AKTIVITAS ANTIMIKROBA BAKTERI ASAM LAKTAT YANG DIISOLASI DARI MAKANAN TRADISIONAL FERMENTASI KHAS BATAK “NANIURA” - Aloysius Aloysius; Anjurniza Ulfa; Anggita Kasih Fianti Situmorang; Harmileni Harmileni; Edy Fachrial (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2019)
Lactic acid bacteria (LAB) could be isolated from various fermented food products. One potential source of LAB is traditional fermented food. The aim of the study was to isolate and investigate antimicrobial activity of LAB isolated from traditional Batak food, “naniura”. The LAB isolates were characterized by Gram staining, fermentation type and catalase test. The investigation of antimicrobial activity of LAB against pathogenic bacteria were conducted using disc diffusion method. The results showed that 6 isolates of BAL were successfully isolated namely BN1, BN2, BN3, BN4, BN5 and BN6 had characteristics of Gram positive, rod shaped and catalase negative. All selected isolate have heterofermentation type. Four isolates (BN1, BN2, BN5 and BN6) were able to inhibit S. aureus, E. coli and S. typhi with inhibition zone diameters ranging from 6,9 to 12,3 cm. Based on the result, it was concluded that LAB isolated from naniura has potential as a source of probiotics.